Crystal structure of 2-(4-bromophenyl)-1,3-dimethyl-2,3-dihydro-1H-perimidine, C19H17BrN2 - Yuan Lin; Li Zhong-Yan; Zhang Min; Yuan Xian-You (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C19H17BrN2, orthorhombic, Pnma, a = 11.506(5) Å, b = 12.176(5) Å, c = 11.327(5) Å, V = 1586.8(11) Å3, Z = 4, Rgt(F) = 0.0409, wRref(F2) = 0.1051, T = 296(2) K.